Three-dimensional thermal model for vertical direct chill slab casting process. (October 2014) - Begum, L.; Hasan, M.
<x content-type="archive" xml:space="preserve">Abstract</x> To aid in the designing of an automatic control system, a steady state three-dimensional (3D) thermal model is developed to predict the temperature distributions for an industrial scale vertical direct chill (DC) slab caster for aluminium alloy AA-1050. A single domain approach for the liquid, mushy and solid regions is used by employing the enthalpy porosity technique. The convective heat transfer in the liquid region is taken into account by assuming a slag flow velocity field equal to the casting speed. The predicted thermal field is verified with the numerically predicted temperature field available in the literature and a reasonably good agreement is found. Detailed parametric study is carried out by varying important parameters of this process. Results of the temperature field, sump depth, mushy zone thickness, shell thickness and local surface heat flux are presented and discussed. Afin d'aider à la conception d'un système de contrôle automatique, on a développé un modèle thermique à 3D en régime permanent pour la prédiction des distributions de température d'une machine de coulée verticale de brames par refroidissement intense et continu (DC) à l'échelle industrielle, pour l'alliage d'aluminium AA-1050. On utilise une approche à domaine unique pour la région liquide, la région pâteuse et la région solide au moyen de la technique d'enthalpie et porosité. On tient compte du transfert de chaleur par convection dans la région liquide en assumant un champ de vitesse d'écoulement de laitier égal à la vitesse de coulage. On vérifie le champ thermique prédit au moyen du champ de température prédit numériquement dans la littérature et l'on obtient un accord raisonnable. On effectue une étude paramétrique détaillée en faisant varier les paramètres importants de ce procédé. On présente et discute les résultats du champ de température, de la profondeur du refoulement, de l'épaisseur de la zone pâteuse, de l'épaisseur de la coquille, et du flux thermique local à la surface.